2014
DOI: 10.11604/pamj.2014.19.276.5304
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with HIV voluntary disclosure of people living with HIV to their steady sexual partner in the Democratic Republic of the Congo: results from a community-based participatory research

Abstract: IntroductionHIV disclosure to a steady sexual partner (SSP) is important both in preventing HIV transmission and improving the quality of life of people living with HIV (PLHIV). Its determinants have been poorly investigated in the Democratic Republic of the Congo. The study objective was to determine factors independently associated with voluntary disclosure to one's SSP in PLHIV receiving services from a Congolese community-based organization (CBO).MethodsA community-based participatory research was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…In the current study, the prevalence of disclosure was 40%, and it was motivated by the need to protect the partners from HIV transmission, to receive support from their partners, and to be honest and truthful to their partners. Consistent with other studies, concern about protecting the sexual partner from HIV infection was the most common motivator for disclosing [ 8 , 11 , 33 ]. Despite the disclosures being motivated by the need for support, less than a tenth of the participants in the study had received support from the partner following disclosure.…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, the prevalence of disclosure was 40%, and it was motivated by the need to protect the partners from HIV transmission, to receive support from their partners, and to be honest and truthful to their partners. Consistent with other studies, concern about protecting the sexual partner from HIV infection was the most common motivator for disclosing [ 8 , 11 , 33 ]. Despite the disclosures being motivated by the need for support, less than a tenth of the participants in the study had received support from the partner following disclosure.…”
Section: Discussionsupporting
confidence: 87%
“…Aims were formulated with the intention of engaging CHWs in many aspects of the research process, including data collection, analysis and dissemination. Zola et al reported that the ‘community based organisation members (CBO), people living with HIV (PLHIV) and researchers were involved, in an equitable partnership’ 18. Community members were trained in research methods and ethics, and then involved in developing the questionnaire and conducting the interviews 18…”
Section: Resultsmentioning
confidence: 99%